Impacts and Challenges of Implementing Ecological Fiscal Transfers: A Systematic Literature Review of Indonesia’s Policies - Anto, Anto; Mappasere, Fatmawati A.; Chandra, Diky (Journal Public Policy, 2024)
The environmental challenges currently facing Indonesia pose a significant obstacle to the country's sustainable development. The 2009 Law on Environmental Protection and Management (No. 32/2009) establishes a legal framework aimed at preserving and protecting the environment. However, budget constraints often hinder effective environmental management. This study investigates the effectiveness of Ecological Fiscal Transfer (EFT) in promoting environmental conservation in Indonesia. A Systematic Literature Review (SLR) methodology was used to analyze 23 relevant studies on this topic. The findings reveal that EFT implementation has a significant positive impact on environmental conservation. The EFT program fosters improvements in environmental quality, encourages active local participation in conservation efforts, and supports sustainable local economic development. Additionally, EFT enhances accountability regarding the use of government funds and improves public service quality, leading to widespread benefits for both society and the environment. Despite these advantages, EFT faces challenges, including a lack of regional mapping of ecological financing needs and difficulties in the absorption and reporting of fiscal transfer funds. This study concludes that while the Ecology-Based Fiscal Transfer (EFT) policy in Indonesia has positively influenced environmental preservation and sustainable development, it still encounters challenges such as the need for enhanced regional fiscal capacity and better coordination. To ensure its effectiveness, it is crucial to improve coherence between central and local policies and to enhance the management of fiscal transfers.